Novel pyrazole compounds for pharmacological discrimination between receptor-operated and store-operated Ca(2+) entry pathways - Schleifer, H (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: Pyrazole derivatives have recently been suggested as selective blockers of transient receptor potential cation (TRPC) channels but their ability to distinguish between the TRPC and Orai pore complexes is ill-defined. This study was designed to characterize a series of pyrazole derivatives in terms of TRPC/Orai selectivity and to delineate consequences of selective suppression of these pathways for mast cell activation. EXPERIMENTAL APPROACH: Pyrazoles were generated by microwave-assisted synthesis and tested for effects on Ca(2+) entry by Fura-2 imaging and membrane currents by patch-clamp recording. Experiments were performed in HEK293 cells overexpressing TRPC3 and in RBL-2H3 mast cells, which express classical store-operated Ca(2+) entry mediated by Orai channels. The consequences of inhibitory effects on Ca(2+) signalling in RBL-2H3 cells were investigated at the level of both degranulation and nuclear factor of activated T-cells activation. KEY RESULTS: Pyr3, a previously suggested selective inhibitor of TRPC3, inhibited Orai1- and TRPC3-mediated Ca(2+) entry and currents as well as mast cell activation with similar potency. By contrast, Pyr6 exhibited a 37-fold higher potency to inhibit Orai1-mediated Ca(2+) entry as compared with TRPC3-mediated Ca(2+) entry and potently suppressed mast cell activation. The novel pyrazole Pyr10 displayed substantial selectivity for TRPC3-mediated responses (18-fold) and the selective block of TRPC3 channels by Pyr10 barely affected mast cell activation. CONCLUSIONS AND IMPLICATIONS: The pyrazole derivatives Pyr6 and Pyr10 are able to distinguish between TRPC and Orai-mediated Ca(2+) entry and may serve as useful tools for the analysis of cellular functions of the underlying Ca(2+) channels.